علاقةُ الإسلام والغرب في الرواية التاريخية: رواية ريتشارد وارين فيلد "سيوف الإيمان" أنموذجاً: Islam and the West Relationship through the Historical Novel: Richard Warren Field’s Novel The Swords of Faith as an Example - Fuad Abdul Muttaleb (JAR, 2024)
This study examines Richard Warren Field’s novel The Swords of Faith (2010) from the perspective of the relationship between Islam and the West. This study stands out for its monitoring of an American novelist’s attempt to shed light on some of the prevailing perceptions of Arabs and Muslims in the West, in light of the repercussions of the events of September 11, 2001 on the relationship between the West and the Islamic East. It deals with the novel that has not yet been translated into Arabic, nor are studies available in Arabic yet, by exploring the story of the conflict drawn by the novel that took place in the past between the two parties and begins with the Battle of Hattin and ends with the failure of the Third Crusade (1188-1192) and the signing of an agreement between Saladin and Richard the Lionheart. Field continues to work as a balanced writer who defends the accused Arabs and Muslims through the scenes of his novel, exposing Western allegations and subjective assumptions about Arabs and Muslims and refuting them, in a distinct artistic, historical, dialogue style in several places in the novel, which are often linked to terrorism, backwardness and a state of hostility against the West. To illustrate this issue, the narrator deliberately formulates a dialogue between two sane characters from opposing camps, Pierre and Rachid that continues until the end of the novel. As a result, this novel can be described as one of the most objective American works in its portrayal of Arab and Muslim issues, as it criticizes intolerance, aggression, and cruelty, calls for understanding, and hints at the possibilities of that relationship in the present and future. The study uses a descriptive and analytical method to explore and comment on aspects of the historical narration of events. It refers to the fictional text as a primary source and to some historical works as secondary references issued on the novel in English or on the relevant period. Keywords: Richard Warren Field, The Swords of Faith, Third Crusade, Saladin, Richard the Lionheart, Islam and the West, Modern American Novel.